IFTM campus Uberaba em face à sociedade digitalizada: uma proposta de desenvolvimento de um plano de comunicação digital - Vicente, Cláudia Aparecida da Costa (2016)
We live in recent years a complete change in technological paradigms and their influence of social and organizational relationship; therefore, it has a fundamental importance the entry of public institutions in digital ambience. This study has started on the need to know the current processes of communication of a federal institution in the city of Uberaba, namely the Federal Institute of Vocational and Technological Education, Campus Uberaba and from these processes to propose solutions in the area of digital communication. First, we did a survey of issues related to the digital area as Cyberspace; Cyberculture; Hypertextuality; Multimedia; Digital Media, as well as the aspects related to organizational communication and public communication. This is a research has a qualitative approach that allowed the realization and the application of questionnaires and interviews with the students, the teachers and the administrative technicians. Subsequently, we analyzed the data with trough selection and classification of categories of analysis according to Bardin's Content Analysis. After the evaluation of the answers we present the Digital Communication Plan with its communicational products and actions to achieve the goal of institutional strengthening IFTM brand and make the IFTM Campus Uberaba recognized institution in the city and region. This report and its product are based theoretically in Kunsch (2009), Duarte (2012), Bueno (2009), among others, whose thoughts on the changes introduced by technology and communication are used as support for the realization of interactive and intermediated strategies through a computer from a reference that signals to image and institutional identity concepts. This work also sought the interface between corporate communication, branding, digital marketing, cyberculture, public communication and technology.